The Impact of Perception of Ease of Use and Security on Consumer Satisfaction and Consumer Loyalty (Empirical Study of DANA Digital Wallet Users in Semarang City) - Ardiansyah, Muhammad Eri; Rizal, Alimuddin (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
This study aims to analyse the impact of perceived ease of use and security on consumer satisfaction and its impact on consumer loyalty of Dana digital wallet users in Semarang City. The data collection method used a questionnaire via google form which was distributed to 100 respondents. Sample selection using purposive sampling criteria. Hypothesis testing was carried out using multiple linear regression tests and with the statistical software SPSS. The research population includes Dana digital wallet users who have made transactions at least three times. The results showed that perceived ease of use and security had a positive and significant impact on consumer satisfaction. The results also show a positive impact of consumer satisfaction on consumer loyalty. This research contributes theoretically in explaining the mechanism of technology adoption in digital products for shaping consumer attitudes. The results provide practical recommendations for digital service providers, especially the determinants of consumer satisfaction and loyalty.